2014
DOI: 10.1161/jaha.113.000670
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CD47 Drives Left Ventricular Heart Failure Through Ca 2+ ‐CaMKII‐Regulated Induction of HDAC3

Abstract: BackgroundLeft ventricular heart failure (LVHF) remains progressive and fatal and is a formidable health problem because ever‐larger numbers of people are diagnosed with this disease. Therapeutics, while relieving symptoms and extending life in some cases, cannot resolve this process and transplant remains the option of last resort for many. Our team has described a widely expressed cell surface receptor (CD47) that is activated by its high‐affinity secreted ligand, thrombospondin 1 (TSP1), in acute injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 69 publications
5
50
0
Order By: Relevance
“…However, TSP1 does not inhibit eNOS/NO signaling in CD47-null vascular cells; in TSP1 or CD47 knockout mice, the level of NO in soft tissue increases, accompanied by raised tissue blood flow in a tissue ischemia model [33]. Sharifi-Sanjani et al found that lack of CD47 provided protection from cardiac stress and alleviated heart failure [34]. TSP1 can not only regulate the CD47, but also can activate the Nox-1 receptor to increases superoxide in vascular and epithelial cells [35,36] Previous research shows that TSP-1 has an inflammatory-associated role in myocardial infarction and MIRI [37] The basic mechanism underlying the effect of CD47 blockade in alleviating MIRI was determined by several in vivo experiments demonstrating that limitation of the CD47/TSP1 signaling pathway can alleviate IRI by increasing eNOS-derived NO signaling.…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
“…However, TSP1 does not inhibit eNOS/NO signaling in CD47-null vascular cells; in TSP1 or CD47 knockout mice, the level of NO in soft tissue increases, accompanied by raised tissue blood flow in a tissue ischemia model [33]. Sharifi-Sanjani et al found that lack of CD47 provided protection from cardiac stress and alleviated heart failure [34]. TSP1 can not only regulate the CD47, but also can activate the Nox-1 receptor to increases superoxide in vascular and epithelial cells [35,36] Previous research shows that TSP-1 has an inflammatory-associated role in myocardial infarction and MIRI [37] The basic mechanism underlying the effect of CD47 blockade in alleviating MIRI was determined by several in vivo experiments demonstrating that limitation of the CD47/TSP1 signaling pathway can alleviate IRI by increasing eNOS-derived NO signaling.…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
“…For instance, Ferguson et al found that class I HDAC inhibition repressed cardiac hypertrophy induced by several pathological insults in vitro via inhibition of ERK1/2 by Dual Specificity Phosphatase 5 (DUSP5) (18). Furthermore, HDAC3 was reportedly involved in different aspects of heart pathologic change, including heart failure (19), hypertrophy (20) and abnormal energy metabolism (21), but so far no information is available for its role in DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated cardiac trabecular muscle from Thbs4 -/-mice showed minimal calcium flux with sustained stretch (32). Conversely, treatment with the CD47-binding peptide 7N3 (10 lM) stimulated a rapid calcium flux in isolated rat neonatal cardiac myocytes (229). Furthermore, Thbs2 -/-mice were more sensitive to doxorubicin-mediated cardiomyopathy than WT mice (284).…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 99%
“…NO dysregulation contributes to LV HF (221), and Nos3 -/-mice experience more LV dysfunction and fibrosis after LV pressure overload than controls (220). TSP1 but not CD47 protein was induced in the left ventricles of WT mice after 4 weeks of transverse aortic constriction (TAC) concurrent with increased histone deacetylase 3 (HDAC3) and calcium/calmodulin-dependent protein kinase II expression, and LV hypertrophy and dysfunction (229). Conversely, Cd47 -/-mice did not develop LV hypertrophy and dysfunction and had less LV HDAC3 expression both before and after TAC.…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 99%